The BREASTrial Stage III: Acellular Dermal Matrix Breast Reconstruction Outcomes from 3 Months to 2 Years Postoperatively. Issue 1 (4th October 2022) - Mendenhall, Shaun D.; Moss, Whitney D.; Graham, Emily M.; Carter, Gentry; Agarwal, Jayant P.
Abstract : Background: The Breast Reconstruction Evaluation of Acellular Dermal Matrix as a Sling Trial (BREASTrial) is a blinded, randomized trial comparing the outcomes of tissue expander breast reconstruction using AlloDerm or DermaMatrix. In this final stage of the trial, outcomes 3 months to 2 years after definitive reconstruction are reported along with patient satisfaction data. Methods: A randomized trial was conducted to compare complication rates between groups of patients who underwent reconstruction with AlloDerm and DermaMatrix. Regression models were used to analyze the impact of matrix type, age, chemotherapy, radiation therapy, and reconstructive type on complication rates. Premastectomy and postmastectomy questionnaires were used to assess patient satisfaction and were also analyzed using regression models. Results: Of the 128 patients (199 breasts) who were randomized in the trial, 108 patients (167 breasts) were available for analysis in stage III. There was no difference in the overall complication rates between the AlloDerm and DermaMatrix groups (6% versus 13.2%; P = 0.3) or the severity of those complications ( P = 0.7). Obesity was a positive predictor for complications, regardless of reconstruction group ( P = 0.02). Patient satisfaction was positive overall and did not grossly vary between AlloDerm and DermaMatrix groups. Conclusions: Findings from the BREASTrial conclude that AlloDerm and DermaMatrix exhibit similar histologic and clinical outcomes. Patient satisfaction is also similar between matrices. Obesity is a predictor of complications, and acellular dermal matrices should be used with caution in these patients. As the largest head-to-head trial comparing two acellular dermal matrices, the BREASTrial contributes to the fund of knowledge regarding acellular dermal matrix supplementation in breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.